Religious Education in a Multicultural Europe Children, Parents and Schools - Smyth, Emer.; Lyons, Maureen; Darmody, Merike; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Drawing on a major EU-funded research project, this book examines how religious/secular beliefs are formed at school and in the family across different European countries, offering insights into key policy issues concerning the place of religion in the school system and illuminating current debates around religion and multiculturalism.
Keywords: Education; Religion; Philosophy and social sciences; International education; Comparative education; Educational sociology; Education and sociology; Sociology, Educational; Religion and sociology; Education; International and Comparative Education; Sociology of Education; Sociology of Education; Sociology of Religion; Philosophy of Education; Religious Studies, general